Recognize Teachersâ Perception of the School-Based Assessment (SBA) Effectiveness in Increasing Studentsâ Achievement in Mathematics - Radzi, Farhana Mohamad; Sawari, Siti Salwa Md (EDUCARE, 2016)
ABSTRACT: In the assessment of Mathematics, the policy makers have noticed that many students were quite able to learn the necessary formula and apply them to the limited range of textbook and test situation; but when faced with novel problem, they fell short and showed that they were far from having understood the relevant concepts and conceptual relations. Therefore, an effective assessment is needed to promote studentsâ mastery of Mathematical thinking through SBA (School-Based Assessment). SBA is a formative assessment which provide the studentsâ progress from one level to another level. Teachers can create a diagnostic measure to detect the studentsâ progress from time to time. This provides an opportunity for teachers to correct any mistakes and improve studentsâ weaknesses immediately, so that these weaknesses are not accumulated. This study sought to recognize the teachersâ perception of the SBA effectiveness in increasing studentsâ achievement in Mathematics. A total of 50 Mathematics teachers from Secondary Schools in Kedah, Malaysia participated in the survey. A 19-items questionnaire was employed to measure teacherâs perception on the SBA effectiveness and studentsâ scores in Mathematics. The data were analysed quantitatively using descriptive statistics and logistic regression. The result showed that the teachersâ perception on the SBA effectiveness in school had no statistically significant relationship with the studentsâ achievement in Mathematics. This finding implied that the teachersâ perception on the effectiveness of SBA practiced in school didnât affect the studentsâ achievement in Mathematics. KEY WORDS: Teachersâ Perception; School-Based Assessment; Mathematics; Effective Assessment; Studentsâ Achievement.Â Â About the Authors: Farhana Mohamad Radzi completed her Master specialize in Educational Psychology and degree in Mathematics at IIUM (International Islamic University of Malaysia) in Gombak, Kuala Lumpur, Malaysia. Siti Salwa Md Sawari is currently Ph.D. Candidate at the Faculty of Islamic Civilization UTM (Malaysia University of Technology) in Kuala Lumpur, Malaysia. Corresponding authors are: farhana.radzi@gmail.com and salwa.sawari@gmail.comHow to cite this article? Radzi, Farhana Mohamad & Siti Salwa Md Sawari. (2016). âRecognize Teachersâ Perception of the School-Based Assessment (SBA) Effectiveness in Increasing Studentsâ Achievement in Mathematicsâ in EDUCARE: International Journal for Educational Studies, Vol.8(2) February, pp.139-146. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (November 27, 2015); Revised (January 27, 2016); and Published (February 28, 2016).